Additive Manufacturing of Devices Used for Collection and Application of Cereal Rust Urediniospores - Pretorius, Zacharias A.; Booysen, Gerrie J.; Boshoff, Willem H. P.; Joubert, Jozua H.; Maree, Gerrie J.; Els, Johan (Frontiers in Plant Science, 2019)
Optimized inoculation procedures is an important consideration in achieving repeatable plant infection when working with biotrophic rust fungi. Several plant pathology laboratories specializing in rust research employ a system where the collection and application of fungal spores are accomplished using an exchangeable gelatin capsule. Urediniospores are collected from erumpent pustules on plant surfaces into a capsule fitted to a cyclone collector controlled by a vacuum pump. By adding light mineral oil to the same capsule, the spore suspension is then sprayed onto plants by means of a dedicated atomizer (inoculator) connected to an air pressure source. Although devices are not commercially available, modern day technologies provide an opportunity to efficiently design and manufacture collectors and inoculators. Using a process called Additive Manufacturing (AM), also known as “3D printing”, the bodies of a collector and inoculator were digitally designed and then laser-sintered in nylon. Depending on availability, copper or aluminum tubes were fitted to the bodies of both devices afterwards to either facilitate directed collection of spores from rust pustules on plant surfaces or act as a siphon tube to deliver the spore suspension contained in the capsule. No statistical differences were found between AM and metal inoculators for spray delivery time or spore deposition per unit area. In replicated collection and inoculation tests of wheat seedlings with urediniospore bulks or single pustule collections of Puccinia triticina and P. graminis f. sp. tritici, the causal organisms of leaf rust and stem rust, consistent and satisfactory infection levels were achieved. Immersing used devices in acetone for 60 sec followed by a 2 h heat treatment at 75°C produced no contaminant infection in follow-up tests.